Intermolecular interactions and characterization of the novel factor Xa exosite involved in macromolecular recognition and inhibition: Crystal structure of human Gla-domainless factor Xa complexed with the anticoagulant protein NAPc2 from the hematophagous nematode Ancylostoma caninum - Murakami, M. T.; Rios-Steiner, J.; Weaver, S. E.; Tulinsky, A.; Geiger, J. H.; Arni, R. K. (Elsevier B.V., 2007)
NAPc2, an anticoagulant protein from the hematophagous nematode Ancylostoma caninum evaluated in phase-II/IIa clinical trials, inhibits the extrinsic blood coagulation pathway by a two step mechanism, initially interacting with the hitherto uncharacterized factor Xa exosite involved in macromolecular recognition and subsequently inhibiting factor VIIa (K-i = 8.4 pM) of the factor VIIa/tissue factor complex. NAPc2 is highly flexible, becoming partially ordered and undergoing significant structural changes in the C terminus upon binding to the factor Xa exosite. In the crystal structure of the ternary factor Xa/NAPc2/selectide complex, the binding interface consists of an intermolecular antiparallel beta-sheet formed by the segment of the polypeptide chain consisting of residues 74-80 of NAPc2 with the residues 86-93 of factor Xa that is additional maintained by contacts between the short helical segment (residues 67-73) and a turn (residues 26-29) of NAPc2 with the short C-terminal helix of factor Xa (residues 233-243). This exosite is physiologically highly relevant for the recognition and inhibition of factor X/Xa by macromolecular substrates and provides a structural motif for the development of a new class of inhibitors for the treatment of deep vein thrombosis and angioplasty. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: factor Xa exosite; nematode anticoagulant protein; selectide inhibitor; factor VIIa/tissue factor complex; inhibition